Social media advertising trends in tourism - Roxana Sârbu; Felician Alecu; Răzvan Dina (Amfiteatru Economic Journal, 2018)
Advertising in our days is moving to the social media since consumers are spending more and more time on such platforms that offer very customized information for each user. Facebook, for example, is trying to bring each person the most meaningful content, which means the advertising is ultra-customized based on the user activity and preferences, but this kind of personalisation can easily have an unpleasant side effect. The advertising for touristic destinations can become very complex by using fine-tuned campaigns triggered by user consumption patterns revealed in the digital world. By adding a button like "buy now", the social media apps can easily integrate important e-commerce features, so the advertising of today is not only about presenting the content but also about instantly buying products and services. This paper highlights the way in which advertising messages emerging social media can quickly have a greatly improved success rate. Research methodology took as its starting point the findings of scientific studies published in the literature, the obtained results being interpreted from the perspective of the authors' personal considerations on the topic of the paper. The conclusions highlight the main trends related to increasing the success rate of advertisements in tourism by using social media and by choosing the most appropriate platforms, advertising methods and buying tools such as augmented and/or virtual reality that allow to experiment in advance a travel package, placing of advertising messages on the platforms with the greatest impact and including the direct purchase options inside the add, so that viewing the message can be immediately followed by the acquisition of the promoted services.
Keywords: D12; D22; M10; M30; 330; social media; tourism services; advertising; online reputation; intrinsic andextrinsic influence factors